Cambodia Education Sector : Public Expenditure Tracking and Quality of Service Delivery Survey - World Bank Group (World Bank, Washington, DC, 2019)
The Ministry of Education, Youth and Sport (MoEYS) and the Ministry of Economy and Finance (MEF), together with key Development Partners, conducted a Public Expenditure Tracking Survey (PETS) and Quality of Service Delivery Survey (QSDS) for the education sector in Cambodia. PETS identify resource use and leakages by examining flows of funds and materials from the central government to local service providers via regional and local governments. QSDS are multi-purpose surveys that examine the efficiency of frontline service delivery and the dissipation of resources by collecting information on service providers and various agents in the system. Several PETS were conducted in Cambodia in the 2005-2013 period. They generally found leakage to be low but the timeliness and consistency of funds delivery to service providers to be poor. This PETS-QSDS will assist the Royal Government of Cambodia in its aim to improve the efficiency and effectiveness of public service delivery through several key reforms. The educational structure of schooling in Cambodia is six years of primary, followed by three years of lower secondary then three years of upper secondary. Prior to primary, there is at least one year for pre-school education. Cambodia also has technical and vocational education, which commences after completion of grade 9. Higher education commences after grade 12.